Efficacy of Manufacturer Recommended Microwave Time Against Listeria monocytogenes in Ready-to-Eat Chicken Products - Morey, A.; Singh , M.; McKee, S.R. (International Journal of Poultry Science, 2012)
This study evaluated the effect of manufacturer-recommended microwave times on Listeria monocytogenes in Ready-to-Eat (RTE) poultry products. Three chicken products including battered and breaded chicken patties, fully cooked chicken breast fillets (both frozen) and chicken sausages (refrigerated) were inoculated with streptomycin-resistant (1500 μg/ml) L. monocytogenes (Brie 1) at low (ca. 4 log10 CFU/ml) and high (ca. 9 log10 CFU /ml) levels. Following 12 h of either frozen or refrigerated storage, random samples (n = 3 of each product) were individually microwaved for recommended time, undercooked and overcooked. Survival of L. monocytogenes after microwaving was determined by spread plating the samples and enumerating bacterial colonies on BHIA+streptomycin (1500 μg/ml). Analysis of variance with Duncans’ grouping was conducted to determine significant differences in survival (α = 0.05). Microwaving the chicken patties inoculated with high levels of bacteria for a recommended time of 1 min increased surface temperature to 64°C-74°C leading to approximately 1-log reduction (p<0.05) of L. monocytogenes. Chicken breast samples and sausages microwaved at 1100 W according to manufacturer’s instruction reduced L. monocytogenes populations below detection limit at high as well as low levels. Although, recommended microwaving times might not always be effective in eliminating L. monocytogenes, its efficacy will depend upon factors such as product type and the level of L. monocytogenes contamination. Reconstitution of RTE foods below recommended times can make them a potential source of Listeria.